Performance Management System of the Company, It’s Peculiarities and Problems of Application in Ukraine - Potiy, V. Z.; Kulish, H. P. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Performance Management (PM) at company level is concerned with actions to achieve formulated goals. PM refers to the strategic and comprehensive approach to enhance the company performance. The article’s objective is to outline the specifics of performance assessment at company level, highlight the essence and classification of main systems for company performance assessment and their implementation mechanisms, determine the PM impact on a company and PM application possibilities in Ukraine. The PM algorithm and capabilities are analyzed. The following conclusions are made: PM is designed to enhance the companies’ capabilities for performance assessment and management at all the levels within the integrated management environment with due consideration to the factor of employees motivation. The assessment of company personnel, based on combination of Key Performance Indicators (КРІ) and competencies, has to be an essential motivating factor for the company employees. Work of the company personnel by PM, apart from the increasing profit and performance, has positive implications for their professional qualities. As a company needs to be successful not only in the current period, but in the long run, it is supposed to improve its PM.